HAK GUNA BANGUNAN ATAS HAK PENGELOLAAN (Suatu Kajian Perolehan Hak dan Perpanjangan Jangka Waktu) - Urip Santoso (Lembaga Penelitian Universitas YARSI, 2019)
Building rights on land can have effect on state land, right-of-management land, andproperty-right land. Building rights on land over right-of-management land can beattained through land-use agreement, whose issuance should be under approval of districtland office. Its extension period should be under written approval of the owner ofmanagement right. This research applies legal-research method, particularly normativelawresearch. This means that it examines an issue based on the existing laws, especially the ones related to land issues. And this research embraces both statute and conceptual approaches. The right to build on a pot of right-of-management land is proceeded by mutual land-use agreement between the owner of management rights and the prospective owner of building rights. The former has the full authority whether or not to approve the extension period for the latter. Also, the former has the capacity to decide the compensation rate, the terms and conditions which the prospective owner of building rights must abide by. The detailed articles on the above aspects should be put in written on a notarized deed or on a sub-rosa deed by the two parties.